Kingdoms of the Empire
1 online resource (240 pages)
Keywords: Since Edward Gibbon, the degree of disruption or gradual change at the end of antiquity has been vehemently debated. Did Rome fall, or was it only transformed. Was the Empire destroyed by barbarians or was its decay inevitable for internal reasons? By carefully formulating answers to these and other seminal questions, Kingdoms of the Empire will prove an indispensable tool to both classical and medieval scholars. This is the first volume in a new and important monograph series, The Transformation of the Roman World .